2006
DOI: 10.1007/s10709-005-1448-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phylogeography of the Atlantic Forest Endemic Sloth (Bradypus torquatus) and the Widespread Three-toed Sloth (Bradypus variegatus) (Bradypodidae, Xenarthra)

Abstract: The comparative phylogeographic study of the maned sloth (Bradypus torquatus) and the three-toed sloth (Bradypus variegatus) was performed using a segment of mitochondrial DNA (mtDNA) control region. We examined 19 B. torquatus from two regions and 47 B. variegatus from three distant regions of Atlantic forest. This first characterization of molecular diversity indicates a great diversity (B. torquatus: h = 0.901 +/- 0.039 and pi = 0.012 +/- 0.007; B. variegatus: h = 0.699 +/- 0.039 and pi = 0.010 +/- 0.006) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 33 publications
4
36
1
10
Order By: Relevance
“…A recent study on Atlantic forest B. variegatus revealed that sloths distributed on northern Atlantic forest are genetically divergent from those from the southern region and represent two distinct populations, each one considered a MU. Each MU is also compounded by a distinct mitochondrial DNA lineage and the divergence among them was attributed to isolation by distance (Moraes-Barros et al, 2006). This was the first phylogeographic study on this species and it shows the necessity of a better understanding of the common three-toed sloth diversity.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A recent study on Atlantic forest B. variegatus revealed that sloths distributed on northern Atlantic forest are genetically divergent from those from the southern region and represent two distinct populations, each one considered a MU. Each MU is also compounded by a distinct mitochondrial DNA lineage and the divergence among them was attributed to isolation by distance (Moraes-Barros et al, 2006). This was the first phylogeographic study on this species and it shows the necessity of a better understanding of the common three-toed sloth diversity.…”
Section: Introductionmentioning
confidence: 89%
“…For comparative purposes, B. variegatus DNA sequences from two regions of Atlantic forest were also included in the analysis. These sequences were previously described in Moraes-Barros et al (2006). DNA was extracted from tissue samples of museum specimens (study skin) by using the protocol described in Moraes-Barros and Morgante (in press).…”
Section: Introductionmentioning
confidence: 99%
“…Taxonomic Note: There are three genetically distinct populations of this species in the states of Bahia, Espírito Santo and Rio de Janeiro (Moraes- Barros et al, 2002Barros et al, , 2006Lara-Ruiz et al, 2008). The northern population (in southern Bahia) might be considered a separate subspecies (Lara-Ruiz et al, 2008), although indistinguishable from the others in external morphology (A.…”
Section: Vulnerable (Vu B2ab(iiiiii))mentioning
confidence: 99%
“…Genetic studies indicate no gene flow between the populations of southern Bahia (Ilhéus) and Espiríto Santo (Santa Teresa), and those of Poço das Antas (Rio de Janeiro). It appears that these populations have been isolated before the anthropogenic fragmentation of habitat, possibly beginning in the Pleistocene (Moraes-Barros et al, 2006;Lara-Ruiz et al, 2008). In general, little genetic diversity is exhibited within individual populations, but the northernmost population (Bahia) is the genetically more diverse (Moraes-Barros et al, 2006;Lara-Ruiz et al, 2008).…”
Section: Vulnerable (Vu B2ab(iiiiii))mentioning
confidence: 99%
See 1 more Smart Citation